Effect of dopaminergic medication on adenosine 2A receptor availability in patients with Parkinson's disease. (May 2021) - Waggan, Imran; Rissanen, Eero; Tuisku, Jouni; Matilainen, Markus; Helin, Semi; Parkkola, Riitta; Rinne, Juha O.; Airas, Laura
Abstract: Objective: To assess the necessity of withdrawing dopaminergic medication in Parkinson's disease (PD) patients for accurate estimation of adenosine 2A receptor (A2A R) availability using [ 11 C]TMSX PET imaging. This was accomplished by studying the short-term effect of the cessation of dopaminergic medication on A2A R availability in non-dyskinetic patients with PD treated with dopaminergic medication. Methods: Eight PD patients (age 67.9 ± 5.6 years; 6 men, 2 women) without dyskinesia were enrolled in this study. A2A R availability was measured using PET imaging with a [7-methyl- 11 C]-(E)-8-(3, 4, 5-trimethoxystyryl)-1, 3, 7-trimethylxanthine ([ 11 C]TMSX) radioligand after a short term cessation of dopaminergic medication (12hrs for levodopa, 24hrs for dopamine agonists and MAO-B inhibitors). Repeated PET imaging was performed while the patients were back 'on' their regular dopaminergic medication (median 13 days after first imaging). Conventional MRI was acquired for anatomical reference. Specific binding of [ 11 C]TMSX was quantified as distribution volume ratios ( DVR ) for caudate, pallidum and putamen using Logan graphical method with clustered gray matter reference region. Results: No significant differences were observed for the DVR s in all three striatal regions between 'on' and 'off' medication states. Strong correlations were also observed between the two states. Statistical equivalence was found in pallidum (TOST equivalence test, p = 0.045) and putamen (TOST equivalence test, p = 0.022), but not in caudate DVR (TOST equivalence test, p = 0.201) between the two medication states. Conclusions: Our results show that dopaminergic medication has no significant short-term effect on the availability of A2A receptors in putamen and pallidum of patients with PD. However, relatively poor repeatability was demonstrated in the caudate. Highlights: [ 11 C]TMSX PET imaging was used to assess striatal Adenosine A2A receptor binding. Eight PD patients were scanned while on and again while off dopaminergic medication. Adenosine A2A binding was stable in putamen and pallidum between the two states. Poor repeatability of Adenosine A2A binding in caudate warrants further exploration.